A chain of π‐stacked molecules in 4‐(2‐chlorophenyl)pyrrolo[1, 2‐a]quinoxaline and a hydrogen‐bonded sheet in (4RS)‐4‐(1, 3‐1, 3‐benzodioxol‐6‐yl)‐4, 5‐dihydropyrrolo[1, 2‐a]quinoxaline. (15th April 2013) - Castillo, Juan C.; Abonía, Rodrigo; Cobo, Justo; Glidewell, Christopher
Abstract : In the molecule of 4‐(2‐chlorophenyl)pyrrolo[1, 2‐ a ]quinoxaline, C17 H11 ClN2, (I), the bond lengths are consistent with electron delocalization in the two outer rings of the fused tricyclic system, with a localized double bond in the central ring. The molecules of (I) are linked into chains by a π–π stacking interaction. In (4 RS )‐4‐(1, 3‐benzodioxol‐6‐yl)‐4, 5‐dihydropyrrolo[1, 2‐ a ]quinoxaline, C18 H14 N2 O2, (II), the central ring of the fused tricyclic system adopts a conformation intermediate between screw‐boat and half‐chair forms. A combination of N—H...O and C—H...π(arene) hydrogen bonds links the molecules of (II) into a sheet. Comparisons are made with related compounds.